Serbia’s approach to the EU and Russia – Implications for its internal and foreign policy - Ana Jović-Lazić; Ivona Lađevac (Međunarodni Problemi, 2023)
This article examines Serbia’s approach to European integration and relations with Russia and its implications for its internal and foreign policy. Serbia’s policy is characterized as a “small state” foreign policy designed to maintain good relations with the EU and Russia, believing that this will help it overcome internal and international challenges. in light of the tense relations between the West and Russia, the article examines how this policy has developed over the last two decades and whether it is sustainable in changed international circumstances. it focuses on the fact that Serbia’s approach toward the EU and Russia has shown continuity despite the growing polarization at the international level caused by the crisis in Ukraine in 2014. However, due to the rapid and dramatic deterioration of EU-Russia relations caused by Russia’s attack on Ukraine, Serbia’s current policy has become very difficult to maintain. Serbia’s pragmatic policy, shaped by internal and foreign political interests and guided by a series of economic, legal, and security arguments, was put to the test. These arguments have emerged as new key trends in Serbia and can be traced through the state’s response to the war in Ukraine and the EU and Russia’s responses to the country’s policy. Serbia found itself under pressure from both sides to choose one side over the other, which causes tension and uncertainty and put the country in a difficult position. This article shows that despite the pressure and expectations of both sides, there was no drastic change in Serbia’s policy towards the EU or Russia. However, the fact is that there is less space for the fulfillment of the country’s foreign policy priorities, which now seem mutually incompatible. Therefore, in a broader sense, this article calls into question the sustainability of Serbia’s current foreign policy as a framework for preserving the strategic and national interests of the country.